Encyclopedia británica, micropedia VOL. 2 / William Benton - Benton, Britannica (1968)
Cross references appar often, identified by see, see also, or as related entres and always refer to other entries in the ready reference; entries are alphabetized as if they were one word up to the comme, regardless of the number of words in the title, thus; direction of index; volume and page numbers immediately following the title of an entry always refer to a comprehensive article in volumes 1 through 9.